Validation of Modified Questionnaire on Knowledge of Human Papilloma Virus Vaccination among Parents - Mohd Sopian, Mastura; Shaaban, Juwita; Mohd Yusoff, Siti Suhaila; Wan Mohammad, Wan Mohd Zahiruddin (2015)
INTRODUCTION: Knowledge on Human Papilloma Virus (HPV) vaccination plays an important role in determining the acceptance of HPV vaccine for the daughters after implementation of HPV vaccine as nation immunisation program since 20101,3. OBJECTIVE: This study aimed to determine the reliability and validity of a modified questionnaire to assess parents’ knowledge on HPV vaccination. METHODS: The study was conducted using self-administered questionnaire in January 2015 among parents of SK Pasir Putih (P). Content and face validity were performed. This questionnaire was modified from previous studies among women in Malaysia (Sami et.al 2010) and parents in Thailand (Archin et.al 2012) with 4 and 9 items respectively on knowledge of HPV infection and HPV vaccine constructs. Construct validity was assessed using factor analysis with varimax rotation while reliability was assessed using Cronbach’s alpha. Data was analysed using SPSS version 22. RESULTS: Sixty-five parents participated in this study. The final model consists of 4 and 9 items with factor loading of 0.59 – 0.78, 0.68 – 0.87, respectively on knowledge of HPV infection and knowledge of HPV vaccine constructs. The Cronbach’s alpha for each construct was 0.64, 0.80 and overall Cronbach’s alpha was 0.86. CONCLUSION: This 13 – item modified questionnaire is reliable and valid to be used for assessing knowledge on HPV vaccination among parents. Keywords: knowledge, HPV vaccine, parents